Transvenous extraction of a 26-year-old Accufix atrial lead using TightRail rotating dilator sheath - Anar Mammadli; Veysel Kutay Vurgun; Onur Yıldırım; Ali Timuçin Altın; Başar Candemir; Ömer Akyürek (KARE Publishing, 2018)
With the increasing number of implanted pacemakers and implantable cardioverter defibrillators, removal is required more frequently. Presently described is the transvenous extraction of a 26-year-old Accufix atrial lead using a mechanical dilator sheath. A 50-year-old male patient was admitted to the clinic with a pacemaker pocket infection. The atrial lead was an Accufix Bipolar J-Atrial active fixation lead, a model that was recalled in 1994, after reports of 2 deaths and 2 nonfatal injuries related to protrusion of the J retention wire. Both the atrial and ventricular leads were extracted using a mechanical dilator sheath. The Pacemaker Lead Extraction with the Excimer Sheath (PLEXES) Trial reported that of the 57 Accufix leads randomized to a non-laser approach, only 47% were removed successfully, compared with 96% of laser-randomized cases. Since laser sheaths are not available in Turkey, use of a mechanical dilator sheath was required. To our knowledge, this is the oldest Accufix lead extracted with a non-laser sheath. During the extraction of the ventricular lead, the tip of the lead broke off inside the right ventricle and the residual part was left inside the heart. During 3 months of follow-up, no signs of infection or any other undesirable events were encountered.